Inside the World of the Eunuch : a Social History of the Emperor's Servants in Qing China. - Dale, Melissa S. (Hong Kong University Press, 2019)
The history of Qing palace eunuchs is defined by a tension between the role eunuchs were meant to play and the life they intended to live. This study tells the story of how a complicated and much-maligned group of people struggled to insert a degree of agency into their lives. Rulers of the Qing dynasty were determined to ensure the eunuchs' subservience and to limit their influence by imposing a management style based upon strict rules, corporal punishment, and collective responsibility. Few eunuchs wielded significant political power or lived in a lavish style during the Qing dynasty. Emascu.